Qualitative data analysis from start to finish - Harding, Jamie (SAGE, 2019)
Helping to bridge the gap between data gathering and data analysis, this book is based on a set of easy-to-follow steps woven throughout the text, enabling students to get stuck in and working with qualitative data fast.